Od Biblioteki Aleksandryjskiej do World Wide Web - Kotuła, Sebastian D. (Biblioteka Uniwersytecka w Poznaniu, 2012)
Celem artykułu jest wykazanie paraleli między WWW a Biblioteką Aleksandryjską. Koncepcyjnie WWW znajduje się pod wpływem wypracowanych w kulturze książki metod i sposobów organizacji i zarządzania informacją. Daje się bowiem wskazać podobieństwo między WWW a bibliotecznym zadaniem zabezpieczenia jak największej spuścizny piśmienniczego dziedzictwa kulturowego ludzkości, tj. zgromadzenia bogactwa informacyjnego in corpore i udostępnienia go in situ. Poza tym przyrost informacji w przestrzeni WWW (powstawanie coraz większej liczby stron WWW) doprowadził do konieczności stworzenia odpowiednich technologii informacyjnych, których zadaniem jest zarządzanie tymi cyfrowymi obiektami. Podczas tworzenia niektórych technologii nawiązano do głównej idei przyświecającej twórcom Biblioteki Aleksandryjskiej, tj. stworzenia pełnego repozytorium informacji. W artykule omówiono te technologie, wskazując konceptualne podobieństwo do Biblioteki Aleksandryjskiej.

The article attempts to show parallels between WWW and the Ancient Library of Alexandria. In its conceptual approach, WWW is very much influenced by the methods, organizational procedures and information management procedures that have been worked out and developed within the book culture. There is a striking similarity between WWW and the principal task to be performed by libraries, which is to preserve and protect as much of the mankind’s cultural heritage as possible, i.e., to collect the multitude of information data in substance and to make it available in one place in situ. Furthermore, the increment of information within the www space (i.e., the increase in the number of WWW pages) has ultimately led to a necessity of a creation of appropriate information technologies that would be capable of managing these digital objects. When some of these technologies were already in the making, some of their authors referred to the main idea that had motivated the creators of the Ancient Library of Alexandria, i.e., the idea of a creation of a full and extensive information repository. The present article discusses these technologies and indicates their conceptual similarities with the Alexandria Library.
From the Ancient Library of Alexandria to the World Wide Web
Keywords: Biblioteka Aleksandryjska; Library of Alexandria; World Wide Web; kultura książki; book culture; repozytorium wiedzy i informacji; repositiory of knowledge and information